Xanthogranulomatous cystitis presenting as hematuria: A case report and review of literature (Indian Journal of Case Reports, 2018)
Xanthogranulomatous cystitis (XC) is a rare benign chronic granulomatous inflammation of the urinary bladder of unknown etiology. Here, we report a rare case of XC in a 54-year-old man who presented with painless hematuria and frequent urination for the past 3 years. His urine culture and sensitivity were positive for Escherichia coli with significant colony count. Contrastenhanced computed tomography showed diffusely thickened urinary bladder with no definitive mass. The patient was subjected to other investigations including cystoscopy and biopsy. All the above investigations confirmed the entity to be XC. An endoscopic resection was performed and he was started on a sulfamethoxazole-trimethoprim combination. The patient was asymptomatic at 3-month follow-up.